Deskripsi Kemampuan Representasi Matematis Siswa SMA Pada Materi Statistika - Rita Sari (Jurnal Dedikasi Pendidikan, 2020)
Mathematical problems can be realized by using mathematical symbols and symbols to be better understood by students. This study aims to determine how students' mathematical representation abilities in statistical material in class X1 of SMA Negeri 1 Bendahara. This research method uses descriptive format. The research sample consisted of 67 students in class XI. The results of the analysis obtained with the instrument are description tests totalling 6 questions. Based on the results of data analysis obtained 54.22% of students can change the model of a problem in a mathematical sentence. 39.55% of students can represent a mathematical problem. 61.93% of students can draw pictures to solve problems. As much as 47.76% of students can take steps in solving a mathematical problem and 74.62% of students can answer questions with words. Overall 55.61% of students can represent mathematical statistics material included in the sufficient category.